The cost of nosocomial infections at the pediatric wards of tertiary hospital - Rogacion, Jossie M
Objectives: To determine the cost of nosocomial infections at the general pediatric wards, from the point of view of patients and hospital administrator. Design: Partial economic evaluation using cost description by review of hospital records. Setting: A urban tertiary care general hospital in Manila, Philippines. Patients: Records of all pediatric patients (0-18 years of age) admitted to two general Pediatric wards from January to December 2000. Measurements: Demographic data; type and number of nosocomial infections; hospital costs ? personal services, maintenance and operating expenses (MOE), cost of laboratory examinations; patient costs ? costs of management, diagnostic tests, food, travel and time lost from work. Results: Two hundred forty-five episodes of nosocomial infections (NI) from 144 patients were identified. Mean age was 32.6 months, with 50% of patients one year old and below. NIs occurred singly in 48% while two NIs were experienced by 38%. The most common NIs were bronchopneumonia, sepsis and urinary tract infection, representing 75% of all NIs. The total cost of the 245 NIs. The total cost of the 245 NIs was computed at P7.1M with P3.8 M shouldered by the patients and P 3.3 M by the hospital resulting in a cost of P49,000.00 per patient of P2,000.00 per patient-day. Cost of antibiotics alone amounted to P2.3 M which was 62 % of the total patient costs and 33% of the entire cost. MIOE constituted the main hospital cost (P1.9M) with 30 patients admitted to PICU accounting for P14. M of the MOE. Single NIs cost P 2.4 M or P35,000.00 per infection. Multiple infections cost P4.6 M accounting for P62.000.00 per patient. Ninety-seven patients (68%) were discharged and 28 (19%) died, all due to causes related to NIs. Sensitivity analysis showed that important variables which can reduced the costs of NI were reduction in hospitalization due to NI by 7-12 days P 1-2 M or 14-29% reduction in total cost); reduction in ICU stay by 7 ½ - 9 days (P1.2 ? 1.6 M or 16 ? 23% cost reduction); completeness of antibiotic doses (P 0.3 ? 1.5 M or 4.5 ? 21 % in savings) and decreasing incidence of NI by 1.5% (P1.5M or 21% cost reduction). Conclusion: From the points of view of the patients and the hospital, the costs of NI?s were considerable. A total of 7.1 M were spent for 245 NI episodes in the year 2000, P3.8 M as patient costs and P3.3 M as hospital costs. These translate to a total of P 15.2 M for all NI?s which occurred in 2000. Important costs contributing to the total cost were the MOE of the hospital; cost of management and the indirect cost of time lost from work, both shouldered by the patients.